A novel hybrid jellyfish algorithm for minimizing fuel consumption capacitated vehicle routing problem - Dana Marsetiya Utama; Bahru Widjonarko; Dian Setiya Widodo (Institute of Advanced Engineering and Science, 2022)
Distribution is a critical activity that must be carefully planned in order to minimize the company's fuel costs. The hybrid jellyfish (HJF) algorithm is proposed in this study to solve the fuel consumption capacity vehicle routing problem (FCCVRP). This problem's objective function is to minimize fuel consumption costs. The proposed HJF algorithm is used in this study to generate optimal fuel consumption through a population and iteration parameter experiment. The experiment results indicate that the HJF increasing parameter has an effect on reducing the total cost of fuel. Additionally, this study presents an algorithm comparison that demonstrates how effectively the proposed HJF algorithm solves FCCVRP.